2020
DOI: 10.20944/preprints202006.0153.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Distribution of COVID-19 in Honduras at the Early Phase of the Pandemic Using Geographic Information Systems (GIS)<strong> </strong>

Abstract: The epidemic of Coronavirus Disease 2019 (COVID-19) have affected all the regions of the world, nevertheless, in some countries there is a lack of studies on its main clinical and epidemiological features. We analyzed the incidence, incidence rates, and evolution of COVID-19 cases in Honduras from February 18-April 24, 2020.Methods: Using daily epidemiological data from surveillance about COVID-19 in Honduras, we calculated the rates of incidence (cases/100,000 population), and developed at national, departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Previous studies also identified similar districts of Bangladesh, for example Dhaka, Narayanganj, Gazipur, Narshingdi, Munshigonj and Manikgonj as hotspots of COVID-19 in terms of infection and related deaths(Islam et al, 2020;Rahman et al, 2020). Other countries also reported the epidemic to affect mostly urban populated centres and municipalities and the capital district(Zambrano et al, 2020) Masrur et al (2020). found that Dhaka is the highest active risk cluster since early April which supports our study.…”
supporting
confidence: 90%
“…Previous studies also identified similar districts of Bangladesh, for example Dhaka, Narayanganj, Gazipur, Narshingdi, Munshigonj and Manikgonj as hotspots of COVID-19 in terms of infection and related deaths(Islam et al, 2020;Rahman et al, 2020). Other countries also reported the epidemic to affect mostly urban populated centres and municipalities and the capital district(Zambrano et al, 2020) Masrur et al (2020). found that Dhaka is the highest active risk cluster since early April which supports our study.…”
supporting
confidence: 90%
“…In the Americas, Melin et al ( 2020 ) drafted the phases through which the pandemic took root in Mexican states; Zambrano et al ( 2020 , Honduras, NPR) noticed that emerging positive cases seemed to come mainly from the biggest urban settlements; Cuartas et al, ( 2020 ) studied the infection pattern in the Colombian city of Cali, while in Brazil Santos et al ( 2020 ) did the same for Rio de Janeiro. Still at the urban scale, but halfway around the world, Kalabikhina and Panin ( 2020 , Russia) estimated the virus propagation speed across the metropolitan area of Moscow.…”
Section: Resultsmentioning
confidence: 99%
“…Health service accessibility was a recurrent issue: by applying big-data raster analysis, some continent-wide studies were carried out to compare the healthcare venue availability (Geldsetzer et al, 2020 ). Finally, a group of papers analyzed the role of chronic conditions and their geographic prevalence in affecting the pandemic trends, treating them as a predictive risk factor (Melin et al, 2020 , Mexico), or seeking statistical correlations at the local level (Ramirez and Lee, 2020 , USA), or in retrospective cohort studies (Zambrano et al, 2020 , Honduras, NPR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning recent pandemic Covid-19, many studies have been presented to furnish relevant information useful to study and characterize this viral infection [16], [17]. For example, authors [18] in used daily epidemiological data from surveillance about COVID-19 in Honduras to calculate the rates of incidence and its developed at national, departmental, and municipal levels by implementing GIS-based maps.…”
Section: Introductionmentioning
confidence: 99%